Monte Carlo Simulations of Powerful Neutron Interaction with Matter for the Goals of Disclosure of Hidden Explosives and Fissile Materials and for Treatment of Cancer Diseases versus their Experimental Verifications - Gribkov, V.A.; Latyshev, S.V.; Miklaszewski, R.A.; Chernyshova, M.; Prokopowicz, R.; Scholz, M.; Drozdowicz, K.; Wiącek, U.; Gabańska, B.; Dworak, D.; Pytel, K.; Zawadka, A.; et al. (IntechOpen, 2011)
None